(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2021)
Philosophy of mind has long ceased to be, if indeed it ever was, the exclusive domain of philosophers. In contemporary thought there is increasing interest in these matters from the point of view of technology. This paper gives a critique of the ideas of Ray Kurzweil and briefly reviews some of the recent trends in the treatment of these questions.